Diagnostic Implication and Clinical Relevance of Dermatomal Somatosensory Evoked Potentials in Patients with Radiculopathy: A Retrospective Study - Nam-Gyu Jo; Myoung-Hwan Ko; Yu Hui Won; Sung-Hee Park; Gi-Wook Kim; Jeong-Hwan Seo (Pain Research and Management)
Objective. Dermatomal somatosensory evoked potentials (DSEPs) are used to evaluate abnormalities of the somatosensory tract. There have been some studies on the diagnostic value of DSEP in radiculopathy, but it is still controversial. The purpose of our study is to evaluate the diagnostic implication and clinical relevance of DSEPs in patients with radiculopathy by comparing DSEP findings to radiculopathy symptoms and intervertebral foramen (IVF) or spinal canal stenosis in lumbar magnetic resonance imaging (MRI). Methods. This retrospective study reviewed the medical records of patients (n = 59) who were examined by DSEP (each L4 and L5 dermatome) and lumbar MRI. Radiculopathy symptoms and DSEPs results were compared. For the evaluation of IVF and spinal canal size, sagittal (each bilateral L4/5 and L5/S1 IVF) and axial MR images were selected at the most stenotic level. The sizes of the IVF and spinal canal were measured by the pixel counts of selected MR images. In addition, stenosis severity was morphologically graded on a 4-point scale. DSEP results were compared with the size and grade of the IVF or spinal canal stenosis. Results. DSEPs showed high sensitivity for radiculopathy symptoms. The IVF size at L4/5 and L5/S1 (pixel counts) was significantly related to either L4 or L5 dermatomal somatosensory pathway dysfunction, respectively. However, spinal stenosis (pixel counts and grade) and IVF stenosis grade were not significantly related to DSEPs. Conclusion. This paper could be helpful in the electrophysiologic diagnosis of lumbar radiculopathy.